2016
DOI: 10.1002/cam4.672
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nrf2 silencing on oxidative stress‐associated intestinal carcinogenesis in mice

Abstract: To assess the risk of colorectal cancer in humans with inactivation of NRF2, Nrf2‐proficient (Nrf2 +/+) and ‐deficient (Nrf2 −/−) mice were exposed to potassium bromate (KBrO3) at concentrations of 750 or 1500 ppm for 52 weeks. Neoplastic proliferative lesions were observed in the small intestine and exhibited accumulations of β‐catenin and cyclin D1. The lesions had characteristics similar to those in experimental models of human hereditary colorectal cancer. An additional 13‐week study was performed to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…This in turn results in greater risk of CRC [35]. Other authors have observed similar results when NRF2 is overexpressed as a consequence of silencing, or as a result of epigenetic changes in this gene [3638, 51]. Another way to induce overexpression of NRF2 is using chemical compounds.…”
Section: Discussionmentioning
confidence: 88%
“…This in turn results in greater risk of CRC [35]. Other authors have observed similar results when NRF2 is overexpressed as a consequence of silencing, or as a result of epigenetic changes in this gene [3638, 51]. Another way to induce overexpression of NRF2 is using chemical compounds.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, treatment with a specific HO-1 inhibitor, ZnPP, reversed the cytoprotective effect of PS under H 2 O 2 -induced oxidative stress, indicating that Nrf2-mediated HO-1 activation is an important route for the cytoprotective activity of PS in H 2 O 2 -treated HaCaT keratinocytes. In addition, Nrf2-deficient mice (Nrf2 -/-) are associated with higher sensitivity to carcinogenesis [35] and are linked with the enhanced metastasis of cancer cells [36], which indicated that Nrf2/HO-1 also attenuated carcinogenesis and the metastasis of cancer cells. Thus, boosting Nrf2/HO-1 activity is a promising target for the treatment of inflammation and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is generally considered as a primary defence mechanism of the cell and a major regulator of cell survival. Nrf2 deficient mice are more susceptible to carcinogenesis 54,55 . Many have reported the chemopreventive effect of Nrf2 in cancer [56][57][58] .…”
Section: Discussionmentioning
confidence: 99%